Contestação - Gonçalves, Sylvia Cristina Arinelli (2006)
The wide defense ensured to the litigants is a predominant factor for jurisdictional provision. The respondent could manifest his/her defense on either procedural or merit nature, with direct and indirect content. After being served the defendant shall have a fifteen-day term to present a response in the ordinary proceeding, which can assume the form of a defendant s initial reply, a cross-complaint, an exception and a legal acknowledgement of the petition. The defendant s initial reply is different from the other two kinds of defendant s response the cross-complaint, a true defendant s counter attack against the petitioner in the same court and proceeding, and the exception consists of a defense due to impediment, suspicion and relative incompetence. The defendant s initial reply is the modality of the defendant s defense consisting of the motion to deny the claim drew up in the petitioner s bill of complaint. It is the main document for the defendant s defense, which should concentrate all manifestations in opposition to the petitioner s claim, consisting of the exposition of facts and rights in which the defendant is based to support the demurrer, excepting those provided in the occurrences such as the exception, the crosscomplaint and the refusal of the value of the matter in dispute. In the initial reply, the defendant can allege a matter of procedural nature, either of a preclusive or a non-preclusive nature, by founding the principle of eventuality applicability in his initial reply, as well as matters of merit can be adduced. If the defendant does not contest the suit, the true facts affirmed by the petitioner will be considered and defendant s right of answer will remain precluded. The defendant s manifestation in the proceeding will influence the sentence passed by the judge, and the absence of manifestation will also have a preponderant role in the lawsuit investigation